RASA, PENAMPILAN, DAN SISA SAYURAN PASIEN ANAK DI RUMKITAL DR. RAMELAN SURABAYA [Vegetables Taste, Appearance, and Waste in Pediatric Patients at Dr. Ramelan Naval Hospital Surabaya] - Padella Dian Julia Armadita; Suzanna Primadona; Trias Mahmudiono (Media Gizi Indonesia, 2019)
Food waste should get the attention because it will contribute to recovery time during illness as fulfilling the energy and nutrients need. Meanwhile, many hospitals are having leftover food more than 20 percent. Internal and external factor have correlation with it. This study aimed to analyze the relation between vegetables taste, appearance and waste vegetables among pediatric patients in Dr Ramelan Naval Hospital, Surabaya. This research was a cross sectional study. The samples were 32 children aged 2-12 years old whom hospitalized in class II and III patient rooms. The primary data was collected by interview and observation. Vegetables waste measured by Comstock form. Chi square test was used to analyze the relation between the taste, appearance and waste of vegetables. The result showed that there was no correlation between vegetables waste with four aspects of taste and five aspect of appearance (p value>0.05). Nonetheless, taste, consistency, platting method, and portion tend to have a big difference on vegetables waste.